Exotic Properties of Carbon Nanomatter: Advances in Physics and Chemistry - Putz, Mihai V (Springer, 2015)
This title reports the state-of-the-art advancements in modeling and characterization of fundamental and the recently designed carbon based nanocomposites (graphenes, fullerenes, polymers, crystals and allotropic forms). Written by leading experts in the field, the book explores the quantification, indexing, and interpretation of physical and chemical exotic properties related with space-time structure-evolution, phase transitions, chemical reactivity, and topology. Exotic Properties of Carbon Nanomatter is aimed at researchers in academia and industry.